2017
DOI: 10.3324/haematol.2017.167080
|View full text |Cite
|
Sign up to set email alerts
|

Single cell immune profiling by mass cytometry of newly diagnosed chronic phase chronic myeloid leukemia treated with nilotinib

Abstract: Monitoring of single cell signal transduction in leukemic cellular subsets has been proposed to provide deeper understanding of disease biology and prognosis, but has so far not been tested in a clinical trial of targeted therapy. We developed a complete mass cytometry analysis pipeline for characterization of intracellular signal transduction patterns in the major leukocyte subsets of chronic phase chronic myeloid leukemia. Changes in phosphorylated Bcr-Abl1 and the signaling pathways involved were readily id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 35 publications
(39 reference statements)
1
23
0
Order By: Relevance
“…To evaluate if the effect of TKIs on intracellular signal transduction targets could provide an explanation with respect to the heterogeneous dynamics of TNT formation in K562 and Kcl-22 cells, both cell lines were treated with the various TKIs for 24 hours and known alterations in central signaling pathways known to be downstream of BCR-ABL1 59 were analyzed using mass cytometry. 60 As expected after TKI treatment, we observed a marked reduction in phosphorylation of several ABL1 downstream signaling targets including CrKL-(Tyr207), STAT5-(Tyr694) and RPS6 (Ser235/236 and Ser240/244) ( Figure 1C). Also, phosphorylation of p38-(Thr180/Tyr182) and STAT3-(Tyr705) were reduced in the two cell lines, but there were no obvious differences in therapy response in the proteins investigated that could provide insight to the observed heterogenous dynamics of TNT formation in K562 and Kcl-22 following nilotinib treatment.…”
Section: Effects Of Tyrosine Kinase Inhibitors (Tkis) On Tnt Formatsupporting
confidence: 81%
“…To evaluate if the effect of TKIs on intracellular signal transduction targets could provide an explanation with respect to the heterogeneous dynamics of TNT formation in K562 and Kcl-22 cells, both cell lines were treated with the various TKIs for 24 hours and known alterations in central signaling pathways known to be downstream of BCR-ABL1 59 were analyzed using mass cytometry. 60 As expected after TKI treatment, we observed a marked reduction in phosphorylation of several ABL1 downstream signaling targets including CrKL-(Tyr207), STAT5-(Tyr694) and RPS6 (Ser235/236 and Ser240/244) ( Figure 1C). Also, phosphorylation of p38-(Thr180/Tyr182) and STAT3-(Tyr705) were reduced in the two cell lines, but there were no obvious differences in therapy response in the proteins investigated that could provide insight to the observed heterogenous dynamics of TNT formation in K562 and Kcl-22 following nilotinib treatment.…”
Section: Effects Of Tyrosine Kinase Inhibitors (Tkis) On Tnt Formatsupporting
confidence: 81%
“…More recently, the use of HDcyto, together with computational tools, highlighted the translational relevance of HD techniques in the precise identification of biomarkers of response to therapy . A recent study showed how HDcyto can predict the response to anti‐PD1 (a monoclonal antibody that targets an inhibitory receptors on activated/exhausted T cells) treatment in different cohorts of patients with melanoma, with crucial implications in terms of patient stratification and precision medicine .…”
Section: Monitoring Biomarkers For Individualized Patient Stratificatmentioning
confidence: 99%
“…In recent years, we witnessed an exponential growth in high‐dimensional (HD) technologies, which resulted in a wide range of medical and biological applications. HD cytometers such as mass cytometry (Cytometry by time of flight, CyTOF) and flow cytometry (hereafter termed HDcyto) can detect more than 40 parameters (with the promise for detection of up to 100 parameters) with single‐cell resolution.…”
mentioning
confidence: 99%
“…These limitations make the expanded panels available in mass cytometry appealing for complex hematologic evaluations. Due to this advantage, several groups have used mass cytometry to assess the cellular and immune make up in patients with heme malignancies including lymphoma (Wogsland et al, 2017), multiple myeloma (Baughn et al, 2017), and CML (Gullaksen et al, 2017; Bandyopadhyay et al, 2017) (Table 1). …”
Section: Mass Cytometry To Assess Hematological Malignanciesmentioning
confidence: 99%